ICT Innovations 2012 Secure and Intelligent Systems - Markovski, Smile; Gusev, Marjan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The present stage of the human civilization is the e-society, which is build over the achievements obtained by the development of the information and communication technologies. It affects everyone, from ordinary mobile phone users to designers of high quality industrial products, and every human activity, from taking medical care to improving the state governing. The science community working in computer sciences and informatics is therefore under constant challenge; it has to solve the new appeared theoretical problem as well as to find new practical solutions. \\ The fourth ICT Innovations Conference, held in September 2012 in Ohrid, Macedonia, was one of the several world-wide forums where academics, professionals and practitioners presented their last scientific results and development applications in the fields of high performance and parallel computing, bioinformatics, human computer interaction, security and cryptography, computer and mobile networks, neural networks, cloud computing, process verification, improving medical care, improving quality of services, web technologies, hardware implementations, cultural implication. In this book the best 37 ranked articles are presented.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).